Effect of Enzyme Supplementation of Palm Kernel Meal and Brewer`s Dried Grain on the Performance of Broilers - Iyayi, Eustace A.; Davies, Bina I. (International Journal of Poultry Science, 2005)
Seventy-two male broiler chickens were randomly distributed into groups of 6 totaling 12 groups. Three diets (Diet 1-Basal, maize-based with no enzyme; Diet 2-BDG + Enzyme-based and Diet 3-PKM + Enzyme-based) were formulated and randomly offered to any 4 of the groups. The aim was to compare the performance of the birds on the enzyme supplemented high fibre diets with those on the maize-based diet with no enzyme supplementation. Weight gain and feed intake were significantly (p<0.05) higher on the enzyme supplemented BDG and PKM diets at the starter phase. At the finisher phase, while feed intake was significantly (p<0.05) increased with enzyme supplementation, the weight gain was not significantly affected. The FCR also did not significantly change with enzyme supplementation at the starter phase, but at the finisher phase, feed conversion was significantly (p<0.05) poorer. Carcass measures did not significantly change with enzyme supplementation. Weight of the pancreas was significantly (p<0.05) increased and that of the kidney significantly (p<0.05) reduced in birds on the enzyme supplemented BDG and PKM diets. Apparent digestibility of crude protein, crude fat and crude fibre was significantly (p<0.05) higher with enzyme supplementation. The cost of feed per kg weight gain was lower in the enzyme supplemented diets only at the starter phase. But at the finisher phase, enzyme supplementation did not have any benefit in terms of feed cost. Enzyme supplementation resulted in the reduction of the amount of maize needed in the diets of the birds by 31% and 52% at the starter and finisher phases, respectively.